Orange-fleshed cucumber to enrich nutrition - Ranjan, Pragya; Gangopadhyay, K. K.; Pandey, Chitra; Srivastava, Rakesh; Meena, B. L.; Dutta, M. (Indian Horticulture, 2019)
India, being the centre of origin for cucumber, is known to be the treasure house of cucumber diversity. The common cucumber is green/white-fleshed and is low in nutritional quality. The orange-fleshed cucumber contains more than ten times carotenoid compared to green/white cucumber and can play a vital role in eradication of malnutrition. Two unique genotypes, collected from Mizoram, have orange flesh. Previously orange-fleshed cucumber was known to be derived from a landrace, Xishuangbanna Gourd, from the Yunnan Province in South-west China. However, this unique genotype is closely related with Indian cucumber germplasm. This could be due to migration of cucumber germplasm from north-eastern part of India to Xishuangbanna, China, since both are geographically close to each other. Orange-fleshed Indian cucumber could be utilized in breeding programme to develop carotene rich cucumber which in turn will play a significant role in meeting global nutritional security.